Pengaruh Peran Guru terhadap Implementasi Kurikulum Merdeka di SMP Negeri 1 Kubung - Sari, Julia Novita; Setiawati, Merika (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2023)
The teacher is someone who has a very important role and is related to the success and quality of education. One of them is the successful implementation of the curriculum. The purpose of this study was motivated by the lack of understanding of some teachers regarding the implementation of the independent curriculum at SMP Negeri 1 Kubung, because the independent curriculum was only implemented at SMP Negeri 1 Kubung at the start of learning in 2022. This study aims to examine the influence of the teacher's role on the implementation of the independent curriculum in Kubung 1 Public Middle School. This type of research is quantitative research. The analysis technique used is Simple Linear Regression. The results of the study show that: there is a positive and significant influence on the role of the teacher on the implementation of the independent curriculum, where tcount > ttable (5.563 > 2.048) is obtained with a significant level of ? = 0.05.